Penteco/Charismatic Worldview of Prosperity Theology - Asamoah, Moses K. (African Educational Research Journal, 2013)
This article reviews the penteco/charismatic concept of material blessing (material prosperity) using the Circle and Chorkor branches of Perez Chapel International of Ghana and the clergy of 7 other charismatic churches in Ghana. This is of particular interest in this contemporary era considering the fact that today the emphasis on prosperity gospel by many Penteco/charismatic clergy is dwindling the spirituality of the flock. Methodological triangulation was used in data collection. Twenty clergy from ten penteco/charismatic churches were sampled and interviewed. Questionnaires were also administered. The thematic analysis started by looking for patterns of meaning and issues of potential interest in the data and harnessing them into meaningful coding schemes or groups. This was followed by sorting the different codes into potential themes and interpreting them. Findings among others are: the Holy Spirit is an indispensable factor in material wealth creation; God is the sole architect of a good prosperity; material prosperity is meant to be used for God's glory. It was also found out that many of the penteco/charismatic church members are materially poor and this is contrary to the prosperity theology of the churches in question.
free
Keywords: Beliefs; Churches; Clergy; Economic Factors; Foreign Countries; Interviews; Poverty; Religious Factors; World Views